DIRECTIONS OF INCREASING THE EFFECTIVENESS OF USING AVIATION EQUIPMENT PERSPECTIVE SAMPLES AT THE EXPENSE OF COORDINATED USE OF MODERN INFORMATION TECHNOLOGIES - Yu. I. Buryak; V. L. Kalinin; M. P. Lyubovnikov (Научный вестник МГТУ ГА, 2016)
System, software technical and technological solutions in the directions of readiness and efficiency increase of the use of aviation equipment through automation of information processes of technical operation at the expense of coordinated use of a complex of modern information technology are proposed. The main advantage of given technology is the ability to obtain and use in "real time" mode a number of important performances of aircraft equipments, metrics of organizational and technological processes etc. in the aircraft lifecycle management system.